2017
DOI: 10.1063/1.4990753
|View full text |Cite
|
Sign up to set email alerts
|

Quasi bound states in the continuum with few unit cells of photonic crystal slab

Abstract: Bound states in the continuum (BICs) in photonic crystal slabs represent the resonances with an infinite quality(Q)-factor, occurring above the light line for an infinitely periodic structure. We show that a set of BICs can turn into quasi-BICs with a very high Q-factor even for two or three unit cell structures. They are explained by a viewpoint of BICs originating from the tight binding of individual resonances of each unit cell as in semiconductors. Combined with a reciprocal-space matching technique, the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 40 publications
1
60
0
Order By: Relevance
“…Also, we note that the earlier studies of high-Q 2D microcavities in the regime of avoided resonance crossing [81] can also be linked to the BIC concept. In the very recent pioneering work [7], Rybin and co-authors proposed a novel class of high-Q nanoresonators realised by tuning the structure parameters into the socalled supercavity regime [39,82], which is based on the destructive interference of several leaky modes according to the Friedrich-Wintgen mechanism. Later, strong mode coupling regime at the quasi-BIC conditions was observed experimentally in microwaves [83].…”
Section: Bound States In the Continuummentioning
confidence: 99%
“…Also, we note that the earlier studies of high-Q 2D microcavities in the regime of avoided resonance crossing [81] can also be linked to the BIC concept. In the very recent pioneering work [7], Rybin and co-authors proposed a novel class of high-Q nanoresonators realised by tuning the structure parameters into the socalled supercavity regime [39,82], which is based on the destructive interference of several leaky modes according to the Friedrich-Wintgen mechanism. Later, strong mode coupling regime at the quasi-BIC conditions was observed experimentally in microwaves [83].…”
Section: Bound States In the Continuummentioning
confidence: 99%
“…on the strength of periodic modulation. The latter can be called quasi-BICs, the term which has recently become widely used in the literature for such modes [53,54]. It is also interesting to see a formation of some of the RSs as a result of a rather strong coupling between WG modes which are close in frequency but belong to different Bragg channels, see e.g in Fig.…”
Section: Origin and Evolution Of The Rss In A Pc Slabmentioning
confidence: 99%
“…Clearly, a resonant mode with an arbitrarily large Q-factor can be obtained if β is chosen to be sufficiently close to β * , and an arbitrarily large local field can be induced by an incident wave with the wavevector β. However, practical applications of the strong field enhancement can be limited by the difficulty of controlling β to high precision, in addition to other practical issues such as fabrication errors [48], material dissipation [43], variations in different periods, finite sizes [49][50][51], etc. In [45], we showed that for symmetric standing waves, which are BICs with β * = 0 and are unprotected by symmetry in the usual sense, the Q-factors of the associated resonant modes satisfy an inverse fourth power asymptotic relation, i.e., Q ∼ 1/|β − β * | 4 .…”
Section: Introductionmentioning
confidence: 99%